The Enjoyment of Knowledge Sharing: Impact of Altruism on Tacit Knowledge-Sharing Behavior - Obrenovic, Bojan; Jianguo, Du; Tsoy, Diana; Obrenovic, Slobodan; Khan, Muhammad Aamir Shafique; Anwar, Farooq (Frontiers in Psychology, 2020)
Knowledge sharing between individuals is a key process for knowledge-intensive organizations to create value and gain a competitive edge. An individual is in the center of a complex set of factors, which are conducive to the knowledge sharing process. The purpose of the empirical study is to explain the interaction mechanisms between personality and knowledge sharing behavior and to examine the mediating effects of willingness to share knowledge and subjective norm. The Theory of Planned Behavior, The Social Exchange Theory and Big Five Personality traits theory, were combined to explain tacit knowledge sharing behavior. A survey strategy and purposive sampling was applied, and the analysis was conducted on the sample of 288 employees from Croatia working on knowledge-intensive tasks, for which high levels of tacit knowledge sharing are characteristic. A standard online questionnaire consisted of items evaluated on a seven-point Likert-scale ranging from Strongly agree (7) to Strongly disagree (1). In the structural model, relationships between altruism, willingness, subjective norm and tacit knowledge sharing were tested. Confirmatory Factor Analysis with Maximum likelihood estimation was performed by using SEM software AMOS version 23. The findings of the study suggest that altruism has a direct impact on tacit knowledge sharing, reaffirming relationship with knowledge sharing, but distinguishing between sharing of different types of knowledge, assessing tacit knowledge sharing as a construct separate from general knowledge sharing. Our findings suggest that willingness to share is a predictive factor of knowledge sharing behavior between employees, having both direct impact on tacit knowledge sharing and being a mediator between the trait of altruism and tacit knowledge sharing. The mediation test also indicated that altruism had an indirect influence on tacit knowledge sharing when subjective norm was a mediator. The findings suggest that personality traits relying on social capital, such as altruism, have more influence on tacit knowledge sharing compared to personality traits that have accentuated intrinsic components. The study contributes to the better understanding of factors stimulating knowledge-sharing behaviors and provides recommendations based on empirical evidence, which may later be applied in the development of knowledge sharing leadership styles, employee hiring, and auxiliary initiatives.